Analysis of an Active/Passive Postural Quiet Stance Regulation Model: Perfect Behavior and Critical Characteristics. Issue 40 (2022) - Ati, Ali El; Boussaada, Islam; Tliba, Sami; Niculescu, Silviu-Iulian
Abstract: In this work, we investigate the human quiet stance regulation problem using a single-link inverted pendulum model in the sagittal plane via the ankle joint's passive/active torques' actions. The active torque consists of ankle muscle contractions that are activated by the delayed action of the Central Nervous System (neural controller). The passive torque is related to the intrinsic mechanical properties of the muscle-tendon-ligament component. The failure of the human quiet stance is then directly related to the failure of one or both types of torques. We propose to model the neural controller as a delayed Proportional-Derivative-Acceleration controller acting on the ankle joint's angular position. By using the multiplicity-induced-dominancy property, the critical time delay of the motor control and the critical ankle-joint stiffness are both investigated.